LRIG1 and squamous epithelial uterine cervical cancer: correlation to prognosis, other tumor markers, sex steroid hormones, and smoking. Issue 2 (1st February 2008) - Lindström, A. K.; Ekman, K.; Stendahl, U.; Tot, T.; Henriksson, R.; Hedman, H.; Hellberg, D.
Abstract : The aim is to evaluate LRIG1 as a prognosis predictor and correlations to cofactors in squamous cell cervical cancer. LRIG1 expression was studied in 128 cervical carcinomas and was compared with expression of nine other tumor markers. Smoking history was registered and pretreatment serum estradiol and progesterone levels were evaluated in 79 women. At clinical stage IB, 58% of the tumors showed LRIG1 expression, but there was a decline by increasing stage (33% in stage IV). Ninety percent of women with stage IB cancer and LRIG1 positivity survived, as compared to 64% without expression ( P = 0.02). LRIG1 expression did not predict prognosis in advanced stages, but in stage IIA there was a marked relative difference, with 75% survival in tumors expressing LRIG1, as compared to 43% in those without. No correlation was found between LRIG1 and the other nine tumor markers studied. A high serum progesterone and smoking correlated to absent LRIG1 expression. We conclude that LRIG1 appears to be a significant prognosis predictor in early-stage cervical cancer, independent of the other tumor markers that were studied. Diminished expression in advanced stages and the inverse correlation to serum progesterone and smoking indicates that LRIG1 is a tumor suppressor in cervix.